Polyphyllin VI screened from Chonglou by cell membrane immobilized chromatography relieves inflammatory pain by inhibiting inflammation and normalizing the expression of P2X3 purinoceptor - Zhenhui Luo; Zhenhui Luo; Tingting Wang; Tingting Wang; Zhenglang Zhang; Zhenglang Zhang; Hekun Zeng; Hekun Zeng; Mengqin Yi; Mengqin Yi; Peiyang Li; Peiyang Li; et al. (Frontiers Media S.A., 2023)
Objective: Inflammatory pain is one of the most common diseases in daily life and clinic. In this work, we analysed bioactive components of the traditional Chinese medicine Chonglou and studied mechanisms of their analgesic effects.Material and methods: Molecular docking technology and U373 cells overexpressing P2X3 receptors combined with the cell membrane immobilized chromatography were used to screen possible CL bioactive molecules interacting with the P2X3 receptor. Moreover, we investigated the analgesic and anti-inflammatory effects of Polyphyllin VI (PPIV), in mice with chronic neuroinflammatory pain induced by CFA (complete Freund's adjuvant).Results: The results of cell membrane immobilized chromatography and molecular docking showed that PPVI was one of the effective compounds of Chonglou. In mice with CFA-induced chronic neuroinflammatory pain, PPVI decreased the thermal paw withdrawal latency and mechanical paw withdrawal threshold and diminished foot edema. Additionally, in mice with CFA-induced chronic neuroinflammatory pain, PPIV reduced the expression of the pro-inflammatory factors IL-1, IL-6, TNF-α, and downregulated the expression of P2X3 receptors in the dorsal root ganglion and spinal cord.Conclusion: Our work identifies PPVI as a potential analgesic component in the Chonglou extract. We demonstrated that PPVI reduces pain by inhibiting inflammation and normalizing P2X3 receptor expression in the dorsal root ganglion and spinal cord.